Sri Lanka : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
EXECUTIVE SUMMARY Sri Lanka's 2009 Stand-By Arrangement was initiated at the onset of the global financial crisis. It also coincided with the ending of the country's decades-old civil conflict. This unusual combination of circumstances made the program subject to very high economic uncertainty. The immediate imperative was to avert a balance of payments crisis- allowing for an orderly exchange rate adjustment and a rebuilding of external reserves- so as to forestall a shock with socially disruptive consequences. Recognizing the role of fiscal imbalances in the crisis, the program called for a fiscal consolidation that could restore debt sustainability. The program also aimed to put in place a framework to resolve problem banks and safeguard financial stability. Viewed through the immediacy of averting an acute external shock, Sri Lanka's program was successful. On economic grounds, Sri Lanka's need was evident. The program provided a catalytic effect to confidence at a crucial time. The balance of payments pressures not only ebbed, they reversed decisively within a few months of the program's inception in recognition a potential 'peace dividend' that the country might reap, as well as the Fund's reassuring presence. In conjunction with these factors, the global environment also improved. As a result, the economy experienced strong growth and lower inflation relative to the preprogram years. Exceptional access, as approved at the program's inception, was appropriate, as was the subsequent re-phasing of purchases to reflect improved conditions. The program concluded in 2012 (following two extensions), marking the completion of Sri Lanka's longest engagement with the Fund. Viewed through the broader prism of achieving longer-term objectives, however, the program's success was partial. Although international reserves were restored to a more comfortable level, exchange rate adjustment has not fully restored external competitiveness, and external vulnerabilities remain high. Thanks to a commendable level of expenditure control by the authorities through most of the program, headline and primary fiscal deficits declined after a large initial slippage. However, the fiscal adjustment was unbalanced-relying completely on expenditure cuts-while revenues continued their long-term decline, straining the future ability to sustain much-needed (and growth inducing) capital expenditure. Also, underlying fiscal and external debt-related vulnerabilities have not been significantly reduced despite improvement in headline numbers. Indeed, by some measures, they may have risen. The program had limited success in reining in the losses of state-owned enterprises. There have been improvements in the financial sector-notably in the area of risk-based supervision-but progress still needs to be made in other areas. To a certain extent, shortcomings with respect to longer-term objectives may reflect the fact that structural impediments were significant-in areas ranging from state owned enterprise reform to revenue administration, as well as the management of domestic liquidity conditions. This made some of the goals too ambitious for the time-frame of the program, despite two extensions. Difficulties encountered during previous attempts that were aimed at tackling these problems may have served to temper such optimism. Yet, in some areas-exchange rate flexibility, and revenue enhancements-policy choices also had a role to play in shaping weaker than envisaged program outcomes. By way of lessons, therefore, this report calls for more careful calibration of program goals. Targets need to be tethered by credible well specified bottom-up measures with attention to their sequencing, matching the degree of commitment. There may also be a case for keeping a sharper distinction between various kinds of Fund facilities for differing circumstances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet